Building Awareness of English Teachers in Malangbong District to Produce Evidence of Independent Teaching - Anne Ratna Suminar; Yustika Nur Fajriah; Amir Hamzah; Dede Mizar (Indonesian Journal of Community Empowerment (IJCE), 2021)
Abstract To develop professionalism, teachers should have the awareness to create teaching works both in the form of research-based articles and teaching materials. From that point, this community service is intended to build awareness of English teachers in Malangbong District, Garut Regency in producing evidence of work in Merdeka Mengajar according to the Merdeka curriculum which is currently being echoed by the government, especially formulated by the Ministry of Education, Culture, Research and Technology. This community service activity was attended by as many as seven English teacher participants in Malangbong District. The method used was in the form of lecture, discussion, and training provided in the form of workshops. This activity resulted in the findings that the workshop participants admitted that they had no work in teaching so far. The questionnaire data also showed that after completing the workshop the participants felt that the Merdeka curriculum appeared more flexible and gave teachers the freedom to work on making teaching materials. After attending the workshop, the participants were aware of applying what they believed was in accordance with the Merdeka curriculum and to create teaching works, as has been illustrated and practiced during the workshop session. Participants also felt that this workshop was educational and fun. Abstrak Untuk meningkatkan profesionalisme, guru hendaknya memiliki kesadaran untuk menghasilkan karya baik dalam bentuk tulisan penelitian maupun bahan ajar. Berangkat dari poin tersebut, pengabdian kepada masyarakat ini ditujukan untuk membangun kesadaran guru bahasa Inggris di Kecamatan Malangbong Kabupaten Garut dalam menghasilkan bukti karya Merdeka Mengajar sesuai kurikulum Merdeka yang saat ini tengah digaungkan oleh pemerintah khususnya dikembangkan oleh Kementerian Pendidikan, Kebudayaan, Riset dan Teknologi (Kemendikbudristek). Kegiatan pengabdian kepada masyarakat ini diikuti oleh sebanyak tujuh peserta guru bahasa Inggris yang ada di Kecamatan Malangbong. Metode yang digunakan adalah berupa ceramah, diskusi dan pelatihan yang diberikan dalam bentuk workshop. Kegiatan ini menghasilkan temuan bahwa para peserta workshop mengakui tidak memiliki karya dalam pengajaran selama ini. Data angket juga menunjukkan bahwa setelah selesai mengikuti workshop para peserta merasa bahwa kurikulum Merdeka terasa lebih fleksibel dan memberikan kebebasan kepada guru untuk berkarya membuat materi ajar. Setelah mengikuti workshop peserta sadar untuk menerapkan apa yang diyakini sesuai dengan kurikulum Merdeka dan menghasilkan karya sebagaimana diilustrasikan dan diperagakan saat pelatihan. Peserta juga merasa kegiatan workshop ini bersifat mengedukasi dan menyenangkan.